(E)-1-{4-[Bis(4-bromophenyl)methyl]piperazin-1-yl}-3-(4-bromophenyl)prop-2-en-1-one - Zhong, Yan (International Union of Crystallography, 2011)
In the title molecule, C(26)H(23)Br(3)N(2)O, the piperazine ring adopts a chair conformation and the C=C double bond has an E configuration. In the crystal, molecules are linked through weak intermolecular C—H⋯O hydrogen bonds.